1980
DOI: 10.1139/p80-073
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced fluorescence and discharge emission spectra of CrO. Rotational analysis of the A5Π–X5Π transition

Abstract: The A5Π–X5Π electronic transition of CrO, near 6000 Å, has been analysed in detail using laser-induced fluorescence and conventional discharge emission spectroscopy. The transition provides the first instance where it has been possible to analyse the rotational structures of quintet electronic states completely. Although the parallel polarization of the transition has prevented the spin–orbit coupling and Λ-doubling intervals from being observed directly, it is shown that sufficient indirect information exists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 0 publications
2
28
1
Order By: Relevance
“…(e) Wavelengths of the band heads derived from spectroscopic constants of Hocking et al (1980): 6451.953 (R 2 ), 6455.191 (R 3 ), 6459.463 (R 4 ), 6465.369 (R 5 ).…”
Section: Reddening Distance Radial Velocitymentioning
confidence: 99%
See 1 more Smart Citation
“…(e) Wavelengths of the band heads derived from spectroscopic constants of Hocking et al (1980): 6451.953 (R 2 ), 6455.191 (R 3 ), 6459.463 (R 4 ), 6465.369 (R 5 ).…”
Section: Reddening Distance Radial Velocitymentioning
confidence: 99%
“…(1) see references in Kamiński et al (2009); (2) Rosen (1970); (3) Schwenke (1998); (4) Phillips (1973); (5) Hocking et al (1980). corresponds to V LSR = 6.5 km s −1 .…”
Section: Referencesmentioning
confidence: 99%
“…However, they are somewhat longer than those from recently reported by Hedgecock et al 21 Hedgecock and coworkers obtained the radiative lifetimes under collisionless condition, whereas our values are obtained under multiple collision conditions. Because of the small energy difference (~55 cm Π Ω ), 9 the longer lifetimes in this work might be ascribed to the efficient collisional mixing among the different substates of CrO (B 5 Π Ω ). 22 The …”
Section: Discussionmentioning
confidence: 89%
“…7 Since the pioneering work of Ninomiya, 8 who analyzed a partially resolved rotational spectrum of the 600 nm band system of CrO, Merer and coworkers generated CrO molecules in the gas phase using a microwave discharge in flowing CrO 2 Cl 2 and He or using a microwave discharge through argon over solid CrO 3 , and analyzed rotational structures of the B Π transition bands. [9][10][11] Debore and Gole generated excited state CrO from the reaction of hot Cr atoms with O 3 and N 2 O, and assigned vibrational band structures of electronic transitions observed in their chemiluminescence spectra. 12 In our previous work, we have reported that the ground state FeO molecules can be easily generated in the gas phase by photolyzing a Fe(CO) 5 /O 2 or N 2 O/He mixture using unfocussed weak UV laser pulses at room temperature and highly unsaturated iron carbonyls are responsible for the formation of ground state FeO molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation